PENGEMBANGAN SISTEM INFORMASI WEBGIS UNTUK PROMOSI WISATA DESA SAMPETAN - Agustinus Budi Santoso; Edy Jogatama Purhita; Roro Dita Hapsari (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
Sampetan Village in Boyolali Regency has significant natural and cultural tourism potential, yet its promotion remains limited due to the lack of an adequate information system. This study designs a WebGIS-based information system using the Rapid Application Development (RAD) method to support digital and interactive tourism promotion. The system integrates Leaflet for map visualization and OpenStreetMap (OSM) as a spatial data source. The results indicate that the developed WebGIS effectively displays tourist sites, facilities, and travel routes, providing easier access to destination information and improving the overall efficiency of tourism promotion in Sampetan Village.